Esensi dan Jenis Tenaga Pendidik dan Kependidikan, Studi Kasus Pengadaan, Pembinaan serta Pemberhentian Tenaga Kerja di Ponpes Wildanul Huda Pagaralam Sumatera Selatan - Faqih Hamzah; Mudofir; Muh. Fatahillah Suparman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research aims to explore the essence and role of educators and educational personnel at Wildanul Huda Islamic Boarding School in Pagaralam, South Sumatra. The research employs a qualitative approach with a case study design. The findings depict the situation at Wildanul Huda Islamic Boarding School in Pagaralam, South Sumatra. The institution's vision encompasses noble objectives, such as educating the nation's children with good morals, noble character, and a profound understanding of Salafu Soleh's teachings. The strategic location and a relatively large number of students have a positive impact on religious education. The organizational structure, involving leaders, teaching teams, and staff, forms a solid framework. The recruitment process for educators includes rigorous selection and scholarship support. Educators come from diverse backgrounds, creating an inclusive educational environment. The training program focuses on improving qualifications and performance. Termination of employment occurs after three consecutive violations without improvement. Performance evaluation includes adherence to the teachings of Ahlu Sunnah and the practices of the Prophet Muhammad. The positive contributions of educators create a positive synergy between the institution's vision and mission. This research contributes to the development of human resources management in Islamic boarding schools, with practical implications for better policymaking in managing educators and educational personnel.